Utilization Focused Evaluation of an ELT Prep Program: A Longitudinal Approach - Ilerten, Ferda; Efeoglu, Gulumser (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2021)
The aim of the current study is to evaluate a preparatory progfram of a foreign language teaching department longitudinally via Patton's Utilization Focused Program Evaluation. More specifically, the study scrutinizes the pros, cons and aspects to be improved in the program, and whether the program contributes to overall English proficiency in two subsequent years. As for the aims of the study 77 students (38 in the first and 39 in the second year) and five instructors were recruited. Data were collected via interviews, English Proficiency tests (i.e., CAE) as pre and posttests in each year and lastly Nominal Group Technique. At the end of the study, both students and instructors confirmed that the program contributed to students' overall English proficiency, which was also supported by the statistically significant difference in comparison of TOYS results in two years. Moreover, it was found out that some aspects need modifications such as teaching four skills in an isolated way, lacking individualized learning, and technical inadequacies. Some agreed remedies for the program as follow: process evaluation instead of TOYS exams, up-to-date and content relevant teaching materials and a fully equipped listening lab. All in all, in addition to many other positive aspects, the study reveals that evaluation that was carried out in the first year involving both students and instructors contributed to students' overall gain in the program in the second year.
Keywords: program evaluation; English Language Teaching; utilization focused evaluation; Education & Educational Research